PELATIHAN PENGELOLAAN E-LEARNING MENGGUNAKAN PLATFORM GOOGLE CLASSROOM DAN MOODLE DI SMPN 1 SECANG DAN SMPN 3 SECANG - Megita Dwi Pamungkas; Fadhilah Rahmawati; Suwito Singgih; Arinda Hikma Wati; Ahmad Syaifudin (LPPM Universitas Bina Bangsa, 2023)
The lack of e-learning management skills carried out during the Covid-19 pandemic has an impact on the administration of e-learning that is not neat, starting from the presentation, learning materials for one semester, assignments and assessments for semester levels and end-of-semester assessments. The problems experienced by partners are because partners, especially teachers at SMPN 1 Secang and SMPN 3 Secang, only know makeshift e-learning without good managerial knowledge. This training activity aims to make trainees get a good understanding in managing e-learning using the google clasroom and moodle platforms. The method of implementing this activity is divided into three main stages, namely planning, implementing and evaluating. The participants of this training consisted of teachers from SMPN 1 Secang and SMPN 3 Secang. The result is that trainees get a good understanding of managing e-learning using the google clasroom and moodle platforms